Menua tetapi berdaya: Peran kewirausahaan lansia dalam mendorong pertumbuhan ekonomi daerah - Husna, Ulya Faiza; Prasetyani, Dwi (Jurnal Riset Ilmu Ekonomi, 2025)
This study examines the influence of silver-entrepreneurship on economic growth in 34 provinces in Indonesia from 2020 to 2024. The influence was analyzed using panel data regression with the Fixed Effect Model Generalized Least Square (FEM-GLS) method. The results show that elderly who remain productive through entrepreneurship do not become an economic burden but contribute positively to regional economic growth. However, the increase in businesses involving paid workers in small-scale enterprises with low productivity tends to weaken growth due to low value-added production. These findings highlight the need for the government to support productive silver-entrepreneurs, for example, by providing business development loans for the elderly to help them run and expand their businesses. Additionally, local governments can implement mentoring programs for the elderly to identify business opportunities, increase worker productivity, and encourage business expansion.